2012
DOI: 10.1155/2012/235929
|View full text |Cite
|
Sign up to set email alerts
|

Design of Deep Belief Networks for Short‐Term Prediction of Drought Index Using Data in the Huaihe River Basin

Abstract: With the global climate change, drought disasters occur frequently. Drought prediction is an important content for drought disaster management, planning and management of water resource systems of a river basin. In this study, a short-term drought prediction model based on deep belief networks (DBNs) is proposed to predict the time series of different time-scale standardized precipitation index (SPI). The DBN model is applied to predict the drought time series in the Huaihe River Basin, China. Compared with BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…3D (depth and shape) analysis [107][108][109][110][111][112][113][114][115] Advanced driver assistance systems [116][117][118][119][120] Animal detection 121 Anomaly detection 122 Automated Target Recognition [123][124][125][126][127][128][129][130][131][132][133][134] Change detection [135][136][137][138][139] Classification Data fusion 191 Dimensionality reduction 192,193 Disaster analysis/assessment 194 Environment and water analysis [195][196][197][198] Geo-information extraction 199 Human detection [200][201][202][203] Image denoising/enhancement 204,…”
Section: References Area Referencesmentioning
confidence: 99%
“…3D (depth and shape) analysis [107][108][109][110][111][112][113][114][115] Advanced driver assistance systems [116][117][118][119][120] Animal detection 121 Anomaly detection 122 Automated Target Recognition [123][124][125][126][127][128][129][130][131][132][133][134] Change detection [135][136][137][138][139] Classification Data fusion 191 Dimensionality reduction 192,193 Disaster analysis/assessment 194 Environment and water analysis [195][196][197][198] Geo-information extraction 199 Human detection [200][201][202][203] Image denoising/enhancement 204,…”
Section: References Area Referencesmentioning
confidence: 99%
“…at is, process data are time series with strong nonlinearities and dynamics, which increases the difficulty of modelling with conventional NNs. Recently, a powerful type of NN named long short-term memory (LSTM) was designed to handle sequence dependence [13][14][15]. An LSTM network is more significant in learning long-term temporal dependencies since its memory cells can maintain its state over a long time and standardize the information moving into and out of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical deep learning approach, deep belief networks (DBN) have attracted wide spread attention and has gained some achievement in the fields of pattern recognition (Nie et al, 2015;Liu et al, 2016) and complex phenomena prediction (Cheng et al, 2017). Some studies also demonstrated that DBN-based drought prediction model (Chen et al, 2012) and algal bloom forecast model (Zhang et al, 2016) have an advantage over the shallow learning approach in respect of generalisation and accuracy.…”
Section: Introductionmentioning
confidence: 99%